2020
DOI: 10.1073/pnas.2002654117
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Zhang et al.: The differential role of LRRK2 variants in nested leprosy phenotypes

Abstract: We thank Dr. Zhang et al. (1) for their thought-provoking comments and addition of exciting results to our recent study that identifies an overlap in the genetic control of type-1 reaction (T1R) and Parkinson's disease (PD) (2). To put the comments by Zhang et al. into context, the purpose and design of our study is to analyze the contribution of rare variants to T1R by contrasting T1R-affected with T1R-free leprosy patients. Our study is not designed to test for common variants or the impact of genetic varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Most studies define TB as a single entity combining cases regardless of their clinical and biological characteristics. While this approach has worked for leprosy ( 210 , 211 ), in other instances combining all leprosy cases has proven troublesome due to the presence of well-defined endophenotypes ( 212 , 213 ). Common endophenotypes in leprosy are excessive host inflammatory responses, so-called lepra reactions, that sub-divide the overall group of patients.…”
Section: Why Have Genetic Studies Of Tb In Humans Been Underwhelming?mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies define TB as a single entity combining cases regardless of their clinical and biological characteristics. While this approach has worked for leprosy ( 210 , 211 ), in other instances combining all leprosy cases has proven troublesome due to the presence of well-defined endophenotypes ( 212 , 213 ). Common endophenotypes in leprosy are excessive host inflammatory responses, so-called lepra reactions, that sub-divide the overall group of patients.…”
Section: Why Have Genetic Studies Of Tb In Humans Been Underwhelming?mentioning
confidence: 99%
“…Endophenotypes can result in misclassification of genetic effects ( 213 , 214 ). Indeed, the genetic associations can be in opposite direction between endophenotype and disease per se ( 212 , 215 ).…”
Section: Why Have Genetic Studies Of Tb In Humans Been Underwhelming?mentioning
confidence: 99%
“…By applying unbiased WGS analysis on a family with monozygotic twins with extreme early-onset leprosy, we identified three coding variants in the LRRK2 and NOD2 genes as strong candidates for contributing to early-onset leprosy susceptibility. Rare and common variants in both genes had previously been associated with leprosy and leprosy reactions by candidate and genome-wide association studies (3,6,7,(24)(25)(26)(27)(28)(29)(30). Intriguingly, the same coding variants identified in the leprosy family have been implicated in reduced susceptibility to PD and CD (8).…”
Section: Discussionmentioning
confidence: 98%
“…In previous work, it was shown that the LRRK2 1628P mutation was a risk factor for leprosy but protective for T1R (6,7). The antagonistic pleiotropic effect of the 1628P LRRK2 mutation is a reflection of the two sides of the anti-pathogen host response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation